2018
DOI: 10.1038/s41598-018-30936-2
|View full text |Cite
|
Sign up to set email alerts
|

Selective Elimination of Human Induced Pluripotent Stem Cells Using Medium with High Concentration of L-Alanine

Abstract: Human pluripotent stem cells, including human induced pluripotent stem cells (hiPSCs), serve as highly valuable sources for both cell-based therapies and basic research, owing to their abilities to self-renew and differentiate into any cell type of the human body. However, tumorigenic risks of residual undifferentiated stem cells limit the clinical application of hiPSCs, necessitating methods to eliminate undifferentiated hiPSCs from differentiated cells. Here, we found that undifferentiated hiPSCs were more s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 21 publications
1
20
0
1
Order By: Relevance
“…Since Gropp et al reported that a teratoma can be established by only a few hundred iPSCs, it is a prerequisite that final products used in regenerative medicine do not contain residual iPSCs when using iPSC-derived cells [17]. To overcome this problem, several strategies have been reported that promote the selective removal of residual iPSCs from a population of differentiated cells, such as the introduction of suicide genes into iPSCs [18], alteration of cell culture conditions [6], and cell sorting using antibodies against cell surface antigens [8]. In these reports, detection procedures for undifferentiated cells included fluorescent labeling, flow cytometry, and methods for confirming teratoma formation in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Since Gropp et al reported that a teratoma can be established by only a few hundred iPSCs, it is a prerequisite that final products used in regenerative medicine do not contain residual iPSCs when using iPSC-derived cells [17]. To overcome this problem, several strategies have been reported that promote the selective removal of residual iPSCs from a population of differentiated cells, such as the introduction of suicide genes into iPSCs [18], alteration of cell culture conditions [6], and cell sorting using antibodies against cell surface antigens [8]. In these reports, detection procedures for undifferentiated cells included fluorescent labeling, flow cytometry, and methods for confirming teratoma formation in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…The fabricated MN chamber was bonded onto the chamber for SkM tissues (27) The completed microdevices were exposed to UV light for at least 2 h for sterilization before use for the coculture. (31). hiPSCs were maintained with Stemfit AK02N on an iMatrix-511 coating (0.5 µg/cm 2 ).…”
Section: Microdevice Design and Fabricationmentioning
confidence: 99%
“…Elimination of these unwanted pluripotent cells is crucial prior to use in the clinical setting. Approaches including positive selection of differentiated cells using specific surface markers [155], selective elimination of residual undifferentiated cells using compounds [156159] or selective media [160, 161], and engineered safety switches such as inducible suicide genes in undifferentiated cells [162, 163], suicide-inducing virus-like particles [164], lectin-toxin fusion protein [165], or microRNA-302 switch [166] could be performed to minimize the risk of tumor formation. More detailed approaches have been extensively reviewed in Jeong et al [167].…”
Section: Challenges and Future Perspectives Of Ipsc Applicationsmentioning
confidence: 99%